People s awareness of circular economy: scale development and relationship with social influence, psychological barriers, and favourable evaluation of sustainable development - Gonella, Jéssica dos Santos Leite (2023)
Circular Economy (CE) encompasses strategies that aim to decouple economic activity from finite resource consumption and eliminate waste from the system as a matter of principle. Supported by a transition to renewable energy sources, the circular model builds economic, natural, and social capital through three principles: eliminate waste and pollution from the start; keep products and materials in use in the supply chain; and regenerate natural systems. The transition to a CE must be initiated by a paradigm shift in the entire supply chain including people. Although this topic is being addressed in several research studies around the world, there are still some research gaps to be filled: (i) Lack of research that considers the analysis of the CE from the perspective of people (bottom-up level), without standardizing on the position these actors occupy in the value chain or the social context in which they are inserted; (ii) the level of depth that CE strategies are dealt with, since the literature points to studies that address specific strategies individually, without delving into the plurality that configures CE; (iii) a lack of a measurement scale to measure people's awareness of CE; (vi) lack of studies in the Brazilian context. Thus, this thesis aims to analyse the factors that interact with people's awareness of CE and their effects on people's favourable evaluation of sustainable development. First, we conducted a Systematic Literature Review (SLR) to map the literature on CE studies. Second, we built and validate a measurement scale to evaluate people’s awareness of CE. After that, we used the validated measurement scale to test two theoretical models. The first presented as its objective assess the effect of Social Influence and Psychological Barriers on People's Awareness of CE. To support our theoretical model and to ground the constructs, we sought inspiration from the Theory of Behavioral Choice (TBC). The second, aimed the analyse the relationship between people's awareness of CE and Favourable Evaluation of people concerning the importance of efforts for sustainable development. To support this theoretical model, we sought inspiration from the Social Learning Theory, which suggests that people learn from their environment and the behaviours of others around them. A survey was applied to 1046 Brazilian respondents through non-probability sampling, and multivariate data techniques (PLS-SEM) were applied. The results of the first model showed that Psychological Barriers (Sunk Costs dragons and Limited Cognition dragons) restrict people's awareness of CE. Besides, it was found that Social Influence (family, friends, and celebrities) positively influence people's awareness of CE. The findings indicate that Social Influence mitigates the negative effect of Psychological Barriers on People's Awareness of CE. The results of the second model showed that people Awareness of CE positively influences favourable evaluation about the importance of Sustainable Development, and the engagement of people and the participation of institutions on Sustainable Development efforts.